Reaffirming Religious Moderation as a Pillar Against Identity Politics in Indonesia - Ahmad Fazar Maulana (Social Impact Journal, 2025)
In recent years, identity politics has been increasingly used in political contests in Indonesia. Identities such as religion, ethnicity, and race are exploited by political actors to gain support, often in ways that divide society. This raises concerns about the disruption of national unity. In such situations, religious moderation becomes an important approach to maintaining social harmony. Religious moderation emphasizes fairness, balance, tolerance, and respect for diversity. This study aims to examine how religious moderation can be a strategy in dealing with identity politics that has the potential to undermine national unity. The method used is a literature study with a descriptive qualitative approach. Data was obtained from scientific journals, books, and relevant national policy documents from the past 10 years. The results of the study show that although the concept of religious moderation has become part of government policy, its implementation in society still faces many challenges, such as a lack of understanding at the community level and the use of religious issues in politics by the elite. Therefore, strategies to strengthen moderation need to be implemented through inclusive education, the involvement of religious and community leaders, digital campaigns that appeal to the younger generation, and the strengthening of social activities that foster cooperation across groups. With these steps, religious moderation can become a real force in building a peaceful, inclusive, and united Indonesia.